LEARNING EVALUATION THROUGH E-LEARNING SOCRATIVE IN LANGUAGE LEARNING - Alfa Mitri Suhara; Dida Firmansyah; Indra Permana (Kopertis Region IV Jabar and Banten, 2019)
The era of industrial revolution 4.0 in the education sector is not enough only with old literacy but it requires three types of literacy, namely data literacy, technology literacy, and human literacy. Therefore, the learning process carried out must be appropriate and following industrial conditions 4.0. One of them is in evaluating learning. Evaluation is carried out to make decisions about the quality of learning that has been carried out, so learning evaluation activities need to use information technology and computers (ICT). It is only through social media e-learning that can be utilized in language learning. This research encourages the improvement of the quality of language learning that uses e-learning media as a learning evaluation medium. The research method used to solve the problem is descriptive qualitative. Meanwhile, the research techniques used were tests and questionnaires. The research was conducted in the Siliwangi IKIP environment with a sample of thirty-three students. Based on the results of the study through tests and questionnaires it was found that 72.2% of language learning evaluations through e-learning media went well, effectively and could be used appropriately.